Research trends on anti-PD-1/PD-L1 immunotherapy for esophageal cancer: A bibliometric analysis - Yang, Yuanyuan; Wang, Feng (Frontiers in Oncology, 2022)
Abstract Objectives: The study aims to summarize publication characteristics of anti-programmed cell death protein 1 (PD-1)/ programmed cell death 1 ligand 1 (PD-L1) immunotherapy for esophageal cancer and create scientific maps to explore hotspots and emerging trends with bibliometric methods. Methods: The publications between 2012 and 2021 were retrieved from the Web of Science Core Collection (WoSCC) on June 20, 2022. Bibliometric tools including HistCite, VOSviewer, and CiteSpace were used for statistical analysis. Data on the trend of the annual output, countries/regions, institutions, journals, authors, subject categories, keywords, and co-cited references were presented in this study. Results: A total of 552 publications written by 3,623 authors of 872 institutions, 44 countries/regions in 250 journals were included in the bibliometric study. China, USA and Japan were the key countries in this field. Kato Ken, Bang Yung-Jue, Frontiers in Oncology, Journal of Clinical Oncology and Natl Canc Ctr were the top 1 productive author, co-cited author, productive journal, co-cited journal and prolific institution, respectively. The top 4 most present keywords were esophageal cancer, immunotherapy, esophageal squamous cell carcinoma and PD-L1. Neoadjuvant chemotherapy, response, PD-1 blockade and CD8+ T cell were four latest research frontiers. The keywords reflected the progress from PD-1/PD-L1 expression to the clinical application of PD-1/PD-L1 inhibitors. The current researches mainly focus on neoadjuvant immunotherapy for esophageal cancer and development of biomarkers. Further research is warranted to determine effective predictive biomarkers or models, illustrate the molecular mechanism of combined treatment, and construct the optimal therapeutic strategy. Conclusions: This study visually analyzed the global trend and hotspots of anti-PD-1/PD-L1 immunotherapy for esophageal cancer over the past decade. The results could guide scientists to comprehensively understand the global frontiers and determine future directions.